Let $k$ be a postive integer number . Then $2k^2+1$ and $3k^2+1$ cannot both be square numbers.

I tried to prove this by supposing one of them is a square number and by substituting the corresponding $k$ value. But I failed to prove it.

  • $\begingroup$ What do you mean by "cannot all be square numbers"? The same as here? $\endgroup$ May 25 '17 at 12:46
  • $\begingroup$ @DietrichBurde I think he means "it is not possible for both $2k^2+1$ and $3k^2+1$ to be perfect squares". $\endgroup$ May 25 '17 at 12:47
  • 3
    $\begingroup$ inequality, where did you get the problem????? $\endgroup$
    – Will Jagy
    May 25 '17 at 15:16
  • 3
    $\begingroup$ Assuming that $2k^2+1=r^2$ and $3k^2+1=s^2$ for some positive integers $k<r<s$ then $(k,r,s)$ is a coprime Pythagorean triple. By the well known parametrization of those (and the fact that necessarily $r$ is odd) we see that there exists natural numbers $m,n$ such that $k=2mn$ and $r=m^2-n^2$ ($s=m^2+n^2$ becomes uninteresting). The equation $2k^2+1=r^2$ then translates to $$1=m^4-10m^2n^2+n^4.$$ It does look like that $\{m,n\}=\{0,1\}$ is the only solution of that (leading to $k=0$), but I don't know how to prove that, One of $m,n$ must be divisible by five, but no cigar :-( $\endgroup$ May 25 '17 at 17:42
  • 1
    $\begingroup$ @GottfriedHelms The reason I called that "uninteresting" is that the Pythagorean stuff made it automatic that $3k^2+1$ is a perfect square (and plugging in $s=m^2+n^2$ yields the same equation). Happy to be proven wrong :-) $\endgroup$ Dec 6 '20 at 18:46

This basically continues from Jyrki Lahtonen's idea in the comment.

Suppose not. The triple $(2k^2+1, k^2, 3k^2+1)$ would be squares of Pythagorean triple, and clearly they are relatively prime (note: NOT mutually coprime). Thus there are $m$, $n$ coprime integers such that

\begin{align} m^2-n^2 &= 2k^2+1 \\ 2mn &= k^2 \\ m^2+n^2 &= 3k^2+1 \end{align}

(Note that among $2k^2+1$ and $k^2$, the latter is clearly the even one.)

There are a lot of ways from here. For example, $2n^2 = k^2$, a contradiction.

  • $\begingroup$ Please typeset the equation in the middle with MathJax. $\endgroup$ Apr 28 '18 at 13:20
  • 3
    $\begingroup$ Maybe I am mistaken, but you said let it be true and then we have $a^2+k^2=b^2$, where $a^2=2k^2+1$, and $b^2=3k^2+1$. Now we know that $a=m^2-n^2, k=2mn, b=m^2+n^2$. Don't you then miss a sqareroot on the right side? $\endgroup$
    – CryoDrakon
    Apr 28 '18 at 13:56
  • 1
    $\begingroup$ Comments can easily and irremediably be deleted. It's a good idea to not "continue" a comment and instead make a self-contained answer. $\endgroup$ Apr 28 '18 at 15:30
  • 2
    $\begingroup$ @HeatTheIce Right! If $2k^2+1=A^2$ and $3k^2+1=B^2$ then $(k,A,B)$ is a primitive Pyth. triplet so $\{k^2, 2k^2+1\}=\{4mn, (m^2-n^2)\}$ and $3k^2+1=m^2+n^2.$.... The squares of a Pyth, triplet cannot also be a Pyth, triplet because $a^4+b^4=c^4$ has no solution in positive integers. $\endgroup$ Apr 28 '18 at 18:55
  • $\begingroup$ Hmm, I think there's something basically wrong. We know, that in $A^2 = 2k^2+1$ there is one solution $A=3,k=2$. So $2mn=k^2=4$ and $mn=2$, and because $m^2-n^2=9$ it must be that $m>n$, so by $mn=2$ we must have $m=2$ and $n=1$. But $2^2-1^2=3$ and not $9$ . So for this case the first two equations lead to a contradiction. $\endgroup$ Jul 20 '18 at 12:12

The two Diophantine equations are equivalent to an elliptic curve with Cremona label "96b1" or LMFDB label 96.a3. The equation of the curve is $\ E: y^2 = x^3 - x^2 -2x = x(x+1)(x-2). \ $ The rational points generate a Klein four-group with points $\ (0,0), (2,0), (-1,0) \ $ along with the point at infinity. There is an algebraic point $\ (3,\sqrt{12}) \ $ of infinite order. Each point on this elliptic curve corresponds to a solution of the system of homogeneous quadratic equations $$ X^2 - Y^2 = 1 W^2, \quad Y^2 - Z^2 = 2W^2, \quad X^2 - Z^2 = 3W^2 $$ which comes from a solution of the system of equations $$ v^2 - u^2 = 1k^2, \quad u^2 - 1 = 2k^2, \quad v^2 - 1 = 3k^2 $$ by dehomogenizing as $\ k = W/Z, \quad u = Y/Z, \quad v = X/Z. \ $ The only rational solutions are $\ k = 0, \quad u = \pm 1, \quad v = \pm 1. $ An infinite family of algebraic solutions is generated by the particular solution $\ W^2 = 1, \quad Z^2 = 1, \quad Y^2 = 3, \quad X^2 = 4. \ $


Update: Just found the solution; see end of text (taken from my other answer )

Not yet an answer, but another ansatz, using transfer-matrices:

A: Let's look at the solutions $3x^2+1 = t^2$ We find $x_0=0$ and $x_1=1$ are the first solutions giving $t_0=1$ and $t_1=2$.
Heuristically the next solutions $x_h=\{0,1,4,15,56,...\} $ and $t_h=\{1,2,7,26,97,...\}$ can be generated by $$\begin{bmatrix}x_0&x_1 \\ t_0&t_1 \end{bmatrix}\cdot M_3 ^h = \begin{bmatrix}x_h&x_{h+1} \\ t_h&t_{h+1} \end{bmatrix}$$ with a transfermatrix $$M_3=\begin{bmatrix} 0&-1 \\1&4 \end{bmatrix}$$

B: Let's next look at the solutions $2y^2+1 = u^2$ We find $y_0=0$ and $y_1=2$ are the first solutions giving $u_0=1$ and $u_1=3$.
Heuristically the next solutions $y_i=\{0,2,12,70,408,...\} $ and $u_i=\{1,3,17,99,577,...\}$ can be generated by $$\begin{bmatrix}y_0&y_1 \\ u_0&u_1 \end{bmatrix}\cdot M_2 ^i = \begin{bmatrix}y_h&y_{i+1} \\ u_h&u_{i+1} \end{bmatrix}$$ with a transfermatrix $$M_2=\begin{bmatrix} 0&-1 \\1&6 \end{bmatrix}$$

C: Now the problem is to show, that $x_h \ne y_i$ for all $h,i>0$. It looks like a combined Pell-problem whose individual solutions are also computable by simple recursions resp. powers of the associated transfermatrices.

Here I tried this by eigendecomposition of $M_3$ and $M_2$ (which leads to Binet-like formulae as they occur for the recursion in the Fibonacci-sequence) but did not yet arrive at a conclusion...

It is interesting to look at the prime-factorizations of the sequences $x_h$ and $y_i$ The primefactors occur periodically with the indexes and a lot of (small) cases can be excluded as possible solutions just by cycle-lengthes of combinations of small primefactors.

Update: Just found the solution; it is arriving at the same observation which was pointed at by @JyrkiLakhonen in his first comment.

Using $3x_h^2 +1 = t_h^2$ and the assumption that there exist an entry $y_i$ in $2y_i^2+1=u_i^2$ such that $y_i=x_h$ and thus $2x_h^2+1=u_i^2$ we can subtract the two equations and get $x_h^2 = t_h^2-u_i^2$ .

This is a pythagorean triple, for which a parametric solution exists in natural numbers$(n,m)>0$. From this we have that $x_h = m^2-n^2$ and $t_h=m^2+n^2$ as Jyrki already mentioned (but dismissed as uninteresting). This says, that the parity of $x_h$ and $t_h$ must be equal to have a solution.

But if we look at the sequences $x_h$ and $t_h$ we see that the parity is always opposite. From this follows that there is no integer solution possible. (The fact that the parity must always be opposite is easy to prove, I think).


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.